2015
DOI: 10.1007/978-3-319-18769-3_4
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Instanton Counting and W-Algebras

Abstract: Basics of the instanton counting and its relation to W-algebras are reviewed, with an emphasis toward physics ideas. We discuss the case of U(N ) gauge group on R 4 to some detail, and indicate how it can be generalized to other gauge groups and to other spaces. This is part of a combined review on the recent developments on exact results on N =2 supersymmetric gauge theories, edited by J. Teschner.arXiv:1412.7121v1 [hep-th]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 171 publications
(250 reference statements)
0
29
0
Order By: Relevance
“…The Nekrasov subfunctions capture the contribution of the various multiplets to the instanton partition function of the four-dimensional [41], five-dimensional [42] or the six-dimensional gauge theories [47][48][49]. For a review of these see [43,50]. The six-dimensional instanton partition function we can identify the different contribution from the tensor or matter multiplets.…”
Section: B Nekrasov Subfunctionsmentioning
confidence: 99%
“…The Nekrasov subfunctions capture the contribution of the various multiplets to the instanton partition function of the four-dimensional [41], five-dimensional [42] or the six-dimensional gauge theories [47][48][49]. For a review of these see [43,50]. The six-dimensional instanton partition function we can identify the different contribution from the tensor or matter multiplets.…”
Section: B Nekrasov Subfunctionsmentioning
confidence: 99%
“…is well-defined and non-singular. In this limit only the mass dependent terms of the conformal weights 15 From now on we simplify the notation by omitting the subscript {ξ 1 , . .…”
Section: The Uv Curvementioning
confidence: 99%
“…Various approaches have been pursued: the geometric description of the low-energy effective actionà la Seiberg-Witten (SW) [2,3], the exact computation of instanton corrections by means of localization techniques [4,5], the relations to integrable models [6], the 2d/4d correspondence also known as the AGT correspondence [7,8], the use of β-ensembles and matrix model techniques [9,10]. Moreover, the string embedding of such theories via geometric engineering has led to the possibility of expressing some relevant observables via topological string amplitudes [11,12] 1 , and further insights 1 We refer to the series of recent review articles [13][14][15][16][17] for an extensive discussion of these topics.…”
Section: Introductionmentioning
confidence: 99%
“…The functions Ψ(a) can be identified with the instanton partition functions (see [36] for a review and references) that were found to be related to Liouville conformal blocks by AGT. The approach proposed in [25] establishes the relation between the wave-functions Ψ(a) in (1.8) and the Liouville conformal blocks without using the relation to the instanton partition functions observed in [33].…”
Section: Jhep10(2015)143mentioning
confidence: 99%